Marxism, modernity, and postcolonial studies - Bartolovich, Crystal; Lazarus, Neil 1953- (Cultural margins, 2002)
At a time when even much of the political left seems to believe that transnational capitalism is here to stay, Marxism, Modernity and Postcolonial Studies refuses to accept the inevitability of the so-called 'New World Order'. By giving substantial attention to topics such as globalisation, racism, and modernity, it provides a specifically Marxist intervention into postcolonial and cultural studies. An international team of contributors locate a common ground of issues engaging Marxist and postcolonial critics alike. Arguing that Marxism is not the inflexible, monolithic irrelevance some critics assume it to be, this collection aims to open avenues of debate - especially on the crucial concept of 'modernity' - which have been closed off by the widespread neglect of Marxist analysis in postcolonial studies. Politically focused, at times polemical and always provocative, this book is a major contribution to contemporary debates on literary theory, cultural studies, and the definition of postcolonial studies